The Legal Strength of the Separation of Joint Assets for the Establishment of a Foundation - Novira, Elyana (International Journal of Social Service and Research, 2025)
This study examines the legal strength of separating joint marital assets (harta bersama) for the establishment of a yayasan (foundation) under Indonesian law. The primary focus is on the legality and validity of asset separation in situations where one spouse allocates a portion of the jointly acquired property (harta bersama) to form a yayasan without obtaining prior consent from the other spouse. Employing a normative juridical approach, supported by statutory, case, and doctrinal analysis, this research analyzes the relevant legal framework, including Undang-Undang Perkawinan No. 1 Tahun 1974 (Marriage Law), Undang-Undang Yayasan No. 16 Tahun 2001 (as amended), and pertinent judicial decisions. The findings indicate that unilateral separation of joint assets (harta bersama) can be subject to legal challenge, particularly when such actions infringe upon the principle of equal rights (kesetaraan hak) of both spouses over shared property. The establishment of a yayasan using harta bersama requires mutual agreement (persetujuan bersama) to prevent potential legal disputes and to ensure the legitimacy of the foundation’s legal standing. This study underscores the necessity for legal certainty and spousal consent (persetujuan suami-istri) in the management of assets for philanthropic purposes, in accordance with the prevailing legal doctrines and statutory provisions.